Activitsts at candlelight vigil - Sahl, Ted (photographer):::Creator::::::::::::
Group portrait of gay and lesbian participants of a candlelight vigil held in front of the Santa Clara County Government Center in support of a sexual preference measure. David Steward poses in the center of group, and is wearing a neck tie. Steward served as a commissioner on the Human Relations Commission.